JURNAL PEKERJAAN SOSIAL : PERAN WALI PEMASYARAKATAN DALAM PERAWATAN DI RUMAH TAHANAN KELAS II B PURWOREJO - arsita putri utama; Moch Zaenal Hakim; Enung Huripah (Politeknik Kesejahteraan Sosial Bandung, 2023)
This reasearch aims to obtain an in-depth picture of the role of Correctional Guardians in the Care of Correctional Inmates at the Class IIB Purworejo State Detention Center which is divided into several aspects, namely: the role of Correctional Guardians in administrative activities, the role of Correctional Guardians in coaching activities and the role of Correctional Guardians. in reporting activities. The method used in this research is descriptive qualitative method. There were four informants, the informants were determined based on purposive sampling or with certain considerations of the researcher. Data collection techniques used are in-depth interviews, observation and documentation studies. The results showed that the role of the Correctional Guardian in the treatment of WBP at the Class IIB Purworejo Rutan had not been carried out in accordance with its main duties and functions. This is because the correctional guardian is busy with other tasks. The inactivity of the role of the correctional guardian causes problems such as the lack of enthusiasm for inmates in coaching activities. In addition, it also prevented the inmates from carrying out coaching activities, the inmates were hampered in applying for conditional leave and parole, and the inmates felt confused when facing the Correctional Observation Team trial. Based on these problems, the researchers analyzed that there are several needs that must be met, namely: Correctional Guardians must understand the main duties and functions of Correctional Guardians. In addition, the correctional guardian carries out his role in administrative activities, coaching activities and reporting activities. The third need is the establishment of a communication forum as a means of overcoming the difficulties faced by the Prisoners (WBP). Source systems that can be utilized in solving problems and meeting needs are the guidance from the Regional Office of the Ministry of Law and Human Rights in Central Java, and Social Workers from the Sahabat Kapas Foundation. Keywords: Correctional, Social Work Correctional